Identification of the Ki-1 antigen (CD30) as a novel therapeutic target in systemic mastocytosis - Blatt, Katharina; Schwaab, Juliana; Reiter, Andreas (Blood, 2015)
The Ki-1 antigen (CD30) is an established therapeutic target in patients with Hodgkin lymphoma and anaplastic large-cell lymphoma. We have recently shown that CD30 is expressed abundantly in the cytoplasm of neoplastic mast cells (MCs) in patients with advanced systemic mastocytosis (SM). In the current study, we asked whether CD30 is expressed on the surface of neoplastic MCs in advanced SM, and whether this surface structure may serve as therapeutic target in SM. As assessed by flow cytometry, CD30 was found to be expressed on the surface of neoplastic MCs in 3 of 25 patients (12%) with indolent SM, 4 of 7 patients (57%) with aggressive SM, and 4 of 7 patients (57%) with MC leukemia. The immature RAS-transformed human MC line MCPV-1.1 also expressed cell surface CD30, whereas the KIT-transformed MC line HMC-1.2 expressed no detectable CD30. The CD30-targeting antibody-conjugate brentuximab-vedotin inhibited proliferation in neoplastic MCs, with lower IC50 values obtained in CD30+ MCPV-1.1 cells (10 µg/mL) compared with CD30− HMC-1.2 cells (>50 µg/mL). In addition, brentuximab-vedotin suppressed the engraftment of MCPV-1.1 cells in NSG mice. Moreover, brentuximab-vedotin produced apoptosis in all CD30+ MC lines tested as well as in primary neoplastic MCs in patients with CD30+ SM, but did not induce apoptosis in neoplastic MCs in patients with CD30− SM. Furthermore, brentuximab-vedotin was found to downregulate anti-IgE-induced histamine release in CD30+ MCs. Finally, brentuximab-vedotin and the KIT D816V-targeting drug PKC412 produced synergistic growth-inhibitory effects in MCPV-1.1 cells. Together, CD30 is a promising new drug target for patients with CD30+ advanced SM.